INDONESIA–NORWAY COOPERATION IN REDUCING CARBON EMISSIONS IN INDONESIA UNDER THE REDD+ SCHEME, 2016–2025 - Desfiani, Shena Firanti; Zulham, Muhammad (BHUVANA: Journal of Global Studies, 2026)
This study examines the cooperation between Indonesia and Norway in reducing carbon emissions through the implementation of the Reducing Emissions from Deforestation and Forest Degradation (REDD+) scheme during the period 2016–2025. This research aims to analyze how the Indonesia–Norway REDD+ partnership operates and contributes to emission reduction efforts in the forestry sector. The study employs a qualitative descriptive method, using document analysis of official reports, policy documents, and secondary literature related to REDD+ implementation. The analysis is framed by Green Theory and international cooperation theory to understand environmental diplomacy and shared responsibility between developed and developing countries. The findings indicate that the result-based contribution (RBC) mechanism plays a crucial role in strengthening forest governance, enhancing transparency through the Measurement, Reporting, and Verification (MRV) system, and encouraging policy consistency in reducing deforestation. The study concludes that the Indonesia–Norway REDD+ cooperation represents an effective model of environmental diplomacy that aligns climate mitigation objectives with sustainable development goals.